Coffes and industrial blends aroma profile discrimination according to the chromatic value - Rodrigues, Carla Isabel Igreja; Hanson, Cristina Máguas; Nogueira, José Manuel Florêncio (Coffee Science - ISSN 1984-3909, 2012)
Different polymeric phases have been used in order to perform roasted coffee aroma analysis although not in a systematic way. Variations in the type of SPME polymer and sample composition make experimental results interpretation difficult and may hinder coffee blend differentiation. In the present work, static headspace solid phase microextraction using carboxen/polydimethylsiloxane polymeric fibre (HS-SPME(CAR/PDMS)) followed by gas chromatography-mass spectrometry (GC-MS), revealed the best analytical performance to characterize the aroma profile of coffees and industrial blends with different chromatic values (64.9, 70.6, 75.3, 86.1 and 89.6). The most relevant classes of aroma compounds founded were pyrroles, ketones, pyrazines, furans, phenolics, pyridines, alcohols and acids, independent of the degree of roasting. By combining the analytical methodology with principal component analysis (HS-SPME (CAR/PDMS)/GC-MS/PCA), important aroma compounds such as 2-furancarboxaldehyde, 2-furanmethanol and acetic acid, allows to discriminate the different degrees of roasting, from light (chromatic value 89.6) to dark (chromatic value 64.9) roast. The proposed analytical approach may help to build aroma profile databases to allow a better evaluation of coffee blend quality, and in controlling the industrial roasting processes.